A recepção da pós-modernidade: análise das diretrizes gerais da ação evangelizadora da Igreja no Brasil de 1996 a 2006 - Costa, Genion Bezerra da (2008)
This is a study about the response to post-modernity by the Catholic Church in Brazil which analyzes it in their General Directives of the Evangelizing Action published by the National Conference of Brazilian Bishops in documents 54, 61 and 71 from 1996 to 2006. Initially the study characterizes, in its general lines, modernity and post-modernity. Afterwards, it presents the history and the structure of the documents. Finally, it analyzes the documents demonstrating systematically the bishops thought as developed in the General Directives. The study characterizes the type of response given to post-modernity in the General Directives. It also points out indicators of post-modernity utilized in the General Directives and seeks to show the understanding given by the documents of the Church to post-modernity, specifically in its practical orientations to evangelizing and pastoral action